A Note on the Effect of Storing on the Glue Shear Strength of Tea Chest Plywood - Bali, B. I.; Gupta, V. K. (Indian Forester, 1980)
A doubt has often been expressed that glue shear strength of standard quality tea-chest plywood is reduced under storage. This paper presents the results of a study to investigate the influence of storing upto about 2 years on the glue shear strength of tea-chest plywood. It has been found that upto one and half year there is very little loss of strength beyond it has gone upto 25.30Â°in some cases.